الخصائص الإسلامية في كتاب اللغة العربية للمرحلة الإبتدائية :دراسة منهجية لإنتاج طالب شامل ومتعدد الثقافات: Islamic Characteristics in the Elementary Arabic Language Textbook: Produce Holistic and Multicultural Students - Ahmad Bahari, Adilah; Ahmad H. Osman, Rahmah; Mohd Ghadzali, Nur Syaheerah; Mohamad Nor, Ain Farhani (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص تناولت هذه الدراسة العمل على تحقيق هدف من أهداف التعليم الإسلامي والصادرة عن المؤتمر العالمي الأول للتعليم الإسلامي في مكة المكرمة عام 1977م ومن أبرز التوصيات في ذلك المؤتمر هو تنفيذ نظامًا تعليميًا شاملاً ومتكاملاً ، إدراكا بأن الأوضاع القائمة في المؤسسات التربوية والتعليمية الحالية في معظم بلاد العالم الإسلامي لا تمثل الصورة الإسلامية، ولا تقوم بدورها الواجب في تنشئة الأجيال على هدى الإسلام عبادة وتصورا وسلوكا. بالإضافة إلى أهمية اللغة العربية في فهم الإسلام ، وتهدف هذه الدراسة كذلك إلى تطبيق الخصائص الإسلامية من القرآن والحديث ومصادر التراث الإسلامي المرتبطة بكل موضوع في الكتاب المدرسي لمناهج المستوى الإبتدائي في ماليزيا. ومن نتائج هذه الدراسة ، أنه يمكن تطبيق قيمة الأسلمة في أحد الموضوعات المختارة وهو "اليوم الرياضي" حيث يتم تعلمه من خلال الكتاب المدرسي اللغة العربية للصف السادس الابتدائي ، ويمكن ربط فهم الإسلام واللغة العربية وتطبيقهما في الحياة اليومية للطالب من خلال منظور عالمي ومتعدد الثقافات. Abstract This study was conducted as a result of the achievement of the goal of Islamic education at the First World Conference on Islamic Education in Makkah Al-Mukarramah in 1977 AD. As one of the most predominant recommendations of that conference is the implementation of a comprehensive and integrated educational system, acknowledging that the current conditions in most countries of the Islamic world's educational and educational institutions do not represent the Islamic image, and do not play their correct role in bringing up generations on the guidance of Islam in worship, perception, and behavior patterns. In addition to emphasizing the significance of the Arabic language in comprehending Islam, this research intends to apply Islamic characteristics derived from the Qur'an and Hadith and related to each topic in the textbook for Malaysian primary school curricula. According to the findings of this study, the value of Islamization can be implemented in the selected topic of the subject: “Sports day” acquired through the Arabic Language textbook for primary 6 and the understanding of Islam and the Arabic language may be linked and applied in the student's daily life from a global and multicultural perspective.